The Impact of Implementing Cadet English Language Skills on Preventing Miscommunication - Virginia Pustya Nautika; Firdaus Sitepu; Intan Sianturi; I'ie Suwondo (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Amid rapid maritime industry growth in Indonesia, effective English communication is vital for cadet safety on ships, regulated by IMO's Standard Marine Communication Phrases (SMCP) to prevent miscommunication. This study aims to analyze the influence of cadet English skills implementation (X) on miscommunication prevention (Y) aboard KM Sabuk Nusantara 101. Employing a quantitative approach with simple linear regression design, the research targeted a population of 23 crew members, using total sampling (n=21). Instruments included Likert-scale questionnaires, observation, and documentation, analyzed via SPSS for validity, reliability, classical assumptions, and regression (Y=23.728+0.509X). Results reveal a significant positive effect (t=13.500, p=0.000, R=0.952, R²=90.6%), with high mean scores for English skills (40.57) and prevention (44.38). In conclusion, enhanced cadet English proficiency substantially reduces miscommunication risks, recommending targeted Maritime English training.